THE USE OF TASK COMPLEXITY IN WRITTEN LANGUAGE PRODUCTION - Optaria, Tri; Mahpul, Mahpul; Sukirlan, Muhammad (TELL - US JOURNAL, 2025)
This research aimed to investigate the significant differences in written language production generated from two different types of tasks between low and high proficiency students. Data were collected from 30 low-proficiency and 30 high-proficiency tenth-grade students using two distinct task types, and analyzed using Repeated Measures ANOVA. The findings revealed statistically significant differences in the CAF (Complexity, Accuracy, and Fluency) measures between the two proficiency groups across both task types. In Task 1, significant differences were found in accuracy and fluency, but not in complexity. In contrast, in Task 2 high and low proficiency students generated significant differences across all CAF aspects. These findings highlight the importance of aligning task complexity with learners' proficiency levels in Task-Based Language Teaching (TBLT) to improve language learning outcomes and support more effective instructional design.